1994
DOI: 10.1007/bf00313586
|View full text |Cite
|
Sign up to set email alerts
|

Silicone allergy in ventriculoperitoneal shunts

Abstract: Reported are the cases of three hydrocephalic patients who developed a clinically heterogenous entity with an allergic rejection of their silicone ventriculoperitoneal shunts. All of the patients had an original presentation indicative of a shunt infection, but laboratory analysis revealed sterile cerebrospinal fluid in all three cases. The typical course included recurrent skin breakdowns over the shunt tract, subsequent infections and development of fungating granulomas. Treatment, with successful resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 14 publications
0
30
1
Order By: Relevance
“…Jimenez et al reported on 3 patients with reaction and skin breakdown overlying the ventriculoperitoneal shunt. 5 The CSF was sterile in all 3 patients, and the histological studies of the surrounding tissues revealed acute and chronic inflammatory changes. Two of the patients had granulomas.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Jimenez et al reported on 3 patients with reaction and skin breakdown overlying the ventriculoperitoneal shunt. 5 The CSF was sterile in all 3 patients, and the histological studies of the surrounding tissues revealed acute and chronic inflammatory changes. Two of the patients had granulomas.…”
Section: Discussionmentioning
confidence: 89%
“…The authors postulated that the etiology of the process was an allergic localized reaction to the Silastic material of the shunt system. 5 Implantation of solid silicone materials is followed by the formation of fibrous tissue with a minimal inflammatory response, forming a "pseudocapsule," which is commonly seen around shunt tracks. Other forms of reaction to silicone materials have been described.…”
Section: Discussionmentioning
confidence: 99%
“…3 Jiminez et al suggested that the body may exhibit all of these reactions to silicone to some extent, depending on the patient's own cellular and humoral immune responses based on his or her human leukocyte antigen genotype. 3 With regard to calcification of VPS catheters in the subcutaneous tissues, 2 mechanisms have been described. One mechanism is metastatic calcification that presents with elevated levels of calcium and phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…There is a report with reference to silicon allergy; however, these children had recurrent skin breakdown over the shunt tract without any abdominal symptoms. [11] Since 1986, we are using latex-free gloves while inserting a VP shunt or excising pseudocysts in patients.…”
Section: Discussionmentioning
confidence: 99%